Design in partnership: Renovation of storefronts in peripheral communities - Broeto Miller, Kátia; Pinheiro Rodrigues, Mauro; Esteves Gomes, Ricardo (Guará Journal, 2025)
This paper describes the development of the extension project (hidden for review), which aims to carry out design initiatives in peripheral communities of the Greater Vitória Metropolitan Region. It is formed through partnerships between Civil Society Organizations of Public Interest (OSCIP), community leaders, design and architecture professionals, and (hidden for review), with the participation of Design students through (hidden for review), resulting in facade painting, urban equipment design, environmental design, visual identity, among other possible initiatives. In 2022 and 2023, the project focused on renovating the facades of businesses in the Território do Bem region, which facilitates communication with the visiting public and thus boosts the businesses of participating entrepreneurs. This paper also seeks to highlight the positive impacts for the communities and students of this interaction process, as well as the successes and failures throughout its development. It also demonstrates that the articulation between different actors suggests that Design can cross boundaries of action, expanding the possibility of dialogue in different contexts, in the same way that it is capable of boosting local businesses.